2022
DOI: 10.1007/s11869-022-01200-4
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to the air quality of Konya City, Turkey

Abstract: Considering an integrated approach to assess all of the measured pollutants in a diurnal, monthly, seasonal, and annual time scales and understanding the mechanisms hidden under low air quality conditions are essential for tackling potential air pollution issues. Konya, located in central Anatolia, is the largest province of Turkey with a surface area of 40,838 km 2 and has different industrial activities. The lack of recent detailed studies limits our information on the underlying air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Yakın & Behçet (2019) prepared an emission inventory of traffic-related air pollutants in Van province and Öztürk & Bayram (2019) presented a detailed investigation of Van provinces air pollutant levels, preferred fuels, and descriptive statistics considering them. In a study by Tayanç et al (2022), air pollutants are evaluated on a daily, monthly, seasonal, and annual time scale in which they investigated the mechanisms that influence low air quality by using air pollutants data from Konya, Türkiye.…”
Section: Literaturementioning
confidence: 99%
“…Yakın & Behçet (2019) prepared an emission inventory of traffic-related air pollutants in Van province and Öztürk & Bayram (2019) presented a detailed investigation of Van provinces air pollutant levels, preferred fuels, and descriptive statistics considering them. In a study by Tayanç et al (2022), air pollutants are evaluated on a daily, monthly, seasonal, and annual time scale in which they investigated the mechanisms that influence low air quality by using air pollutants data from Konya, Türkiye.…”
Section: Literaturementioning
confidence: 99%
“…The regional assessment of air quality in different regions of Türkiye, determination of air quality indices, and evaluation of major air pollutants and their interactions have been the focus of many studies and have provided comprehensive information on the spatial and temporal variations of air pollutants in Türkiye [9][10][11]. Studies examining air pollution in Türkiye, such as those conducted by Tayanç et al (2022) [12] and Akan A. (2022) [13], have evaluated the air quality of cities such as Konya and Zonguldak.…”
Section: Introductionmentioning
confidence: 99%
“…Many AQ studies have been conducted in Istanbul, the province with the densest population in Türkiye (Ozdemir, 2014(Ozdemir, , 2019Flores et al, 2020;Efe et al, 2022), and relatively fewer studies are available for other cities of Türkiye. Tayanc et al (2022) statistically analysed the temporal and spatial variability of hourly CO, NO 2 , NO x , PM 10 , PM 2.5 , and SO 2 measured at ve different stations in Konya province between 2008 and 2018. They found that the pollutant with the highest value in Konya was particulate matter.…”
Section: Introductionmentioning
confidence: 99%